Penyisihan Kadar COD Dan TSS Pada Limbah Cair Pewarnaan Batik Mengunakan Metode Elektrokoagulasi - Yesi Arnita; Shinta Elystia; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Wastewater from the textile industry has adverse effects on the environment if disposed of into the waters without any processing. Naphtol is one of the sources of pollutant wastewater coloring batik. Electrocoagulation is one of the alternative method of processing wastewater textiles. This research aims to know the efficiency decreased levels of COD and TSS contained in wastewater through the process electrocoagulation. Research carried out in batch by using aluminium as electrodes that size 17cm by 17cm x 3cm. The size of the reactor electrocoagulation is 30cm x 25cm x 25cm, 1 cm electrode spacing and waste from Volume 10 L. The voltage used was 10, 15, and 20 volts and then sample taken on 15, 30 and 45 minutes while electrodes from the electricity. The analysis showed a decrease in concentration on the parameters of the tested where the span of the efficiency of the allowance for a maximum range of the COD (80-00, 98, 20 %) and TSS (90, 83 % - 95, 83 %). This condition occurs at the time of tension 20 volts in 45 minutes. Based on the Anova to use SPSS.16, found that the voltage and time factor affecting the decrease in the concentration of 94.8% COD and TSS 93.1%. The rest is affected by unknown factors.Keywords: Electrocoagulation, wastewater batik, voltage, contact time, COD